Regional Differences in the Gut Microbiota and Gut-Associated Immunologic Factors in the Ileum and Cecum of Rats With Collagen-Induced Arthritis - Xu, Huihui; Cao, Jinfeng; Li, Xiaoya; Lu, Xiangchen; Xia, Ya; Fan, Danping; Zhao, Hongyan; Ju, Dahong; Xiao, Cheng (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is a common autoimmune disease characterized by chronic inflammation and a multifactorial etiology. We previously showed that gut microbiota dysbiosis in the rat ileum is involved in the development of collagen-induced arthritis (CIA). The gut microbiota in the distinct gastrointestinal tract (GIT) plays region-specific roles, but information on the different roles of the microbiota in distinct GIT compartments of CIA rats is limited. This study aimed to evaluate the region-specific differences in the gut microbial communities and certain gut-associated immunologic factors in the ileum and cecum of CIA rats. Ileal and cecal digesta were collected from CIA and control rats for microbiome analysis. We determined the microbial richness, diversity and taxa as well as the expression of interleukin (IL)-1β and IL-17A in the epithelium and lamina propria of the ileum and cecum mucosal layers. The CIA-induced microbiota alterations in the ileum differed from those in the cecum. The ileal microbiota were more markedly influenced in CIA, as revealed by sharp reductions in the abundances of the families Enterococcaceae, Lactobacillaceae and Streptococcaceae and the genera Lactobacillus and Lactococcus. Moreover, significant increases in IL-1β, and IL-17A mRNA expression were detected in only the ileal epithelium and lamina propria of the mucosal layer. Therefore, the microbial characteristics in the ileum were consistent with the immune-mediated inflammatory features of CIA, suggesting that the ileal microbiota might better represent the CIA-induced inflammatory responses than the cecal microbiota and that these responses might partially impact the progression of RA by regulating intestinal mucosal immunity.